Transforming Human Resource Management with AI: Challenges and Possibilities (Global Journal of Management and Business Research, 2025)
Abstract- Human capital is a vital asset in today s competitive world essential for enhancing workplace performance and effectiveness To enhance employee performance and gain a competitive edge firms must adopt innovative human resource practices Very shortly human resource manage-ment HRM will transition from conventional practices to the most advanced ones including augmented intelligence automation robotics and artificial intelligence AI This literature analysis was conducted to examine the potential opportunities and challenges of practice The proliferation of AI-based HRM practices over the past ten years has prompted a new series of research studies on the consequences of AI adoption on both human and corporate outcomes as well as the evaluation of AI-based HRM practices The way we work is organized in businesses as a result of the adoption of these technologies AI has the power to fundamentally decide how we live or life and work The AI facilitates the HRM with both an opportunities and challenges Today s HR experts are more focused on maximizing the interaction between human and automated work to provide a straightforward and understandable working environment that provides adequate time to improve their performance
Keywords: artificial intelligence; human resource management; augmented intelligence; robotics; auto-mation